The Effect of Teacher Caring Behavior and Teacher Praise on Students’ Engagement in EFL Classrooms - Sun, Yadi (Frontiers in Psychology, 2021)
The emergent respect for the prominence of engagement in the present education has made it one of the most widespread inquiry issues that it has been labeled as ‘the holy grail of learning’ (Sinatra, Heddy, & Lombardi, 2014, p. 1). In the language teaching field, the idea of student activities for learning is intensely rooted in the prevailing standards of effective language learning, which considers language communication and interaction as analytical for language improvement. Moreover, the role of the teachers as the most central figures on the learning prospect is at the center of attention (Pishghadam, Derakhshan, Zhaleh, Al-Obaydi, 2021), and their proficient accomplishment regulates to a large extent the final achievement of both learners and the education process altogether (Mercer & Dörnyei, 2020). However, there is an absence of research which have considered teachers’ care and praise among all positive interpersonal behavior and its significant effect on students’ engagement. So, the present review attempts to focus on teacher care and praise, and their effects on student engagement in EFL classrooms. Subsequently, some implications are presented to clarify the practice of teachers, students, teacher educators, materials developers.